Quality of life of patients with intestinal stoma - Cierzniakowska, Katarzyna; Kozłowska, Elżbieta; Szewczyk, Maria T.; Banaszkiewicz, Zbigniew; Szymańska, Hanna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
The aim of the study was to assess the quality of life of people with a stoma. Material and methods: The research was conducted in a group of 57 adults who had the intestinal stoma formed for minimum 6 months prior to research. The study took place at the Stoma Clinic of University Hospital no. 2 in Bydgoszcz. The proper research tool was the WHOQOL-BREF questionnaire. Results : In the study, 60% of respondents defined their quality of life as very good and good, and 40% as neither good nor bad. The majority of respondents (56%) were very satisfied or satisfied with their health and 30% chose “neither satisfied nor unsatisfied” option. The conclusion is that the quality of life of people with colostomy is worse, especially in the somatic domain (p < 0.05). The time since the stoma was formed significantly worsens the quality of life described in the questionnaire in psychological (p = 0.015) and environmental (p = 0.008) domains. Activities connected with individual nursing of stoma are carried out by 82% of respondents. Also their age influences mainly social and environmental spheres (p < 0.05). Conclusions: 1. More than a half of respondents described their quality of life as good. 2. Patients with ileostomy had higher quality of life than patients with colostomy. 3. Respondents with a possibility of reconstruction of their gastrointestinal tract had higher quality of life in psychological and environmental domains.